Incidence rate of mortality and its predictors among tuberculosis and human immunodeficiency virus coinfected patients on antiretroviral therapy in Ethiopia: systematic review and meta-analysis - Derseh, Nebiyu Mekonnen; Agimas, Muluken Chanie; Aragaw, Fantu Mamo; Birhan, Tilahun Yemanu; Nigatu, Solomon Gedlu; Alemayehu, Meron Asmamaw; Tesfie, Tigabu Kidie; Yehuala, Tirualem Zeleke; Godana, Tilahun Nega; Merid, Mehari Woldemariam (Frontiers in Medicine, 2024)
Abstract Background: Tuberculosis (TB) is the leading cause of death among HIV-infected adults and children globally. Therefore, this study was aimed at determining the pooled incidence rate of mortality and its predictors among TB/HIV-coinfected patients on antiretroviral therapy (ART) in Ethiopia. Methods: An extensive database search was done via PubMed, EMBASE, SCOPUS, ScienceDirect, Google Scholar, and Google from the time of idea conception on March 1, 2023, to the last search via Google on March 31, 2023. A meta-analysis was performed using the random-effects model to determine the pooled incidence rate of mortality and its pooled hazard ratios (PHR) of predictors among TB/HIV-coinfected patients on ART. The sources of heterogeneity were assessed and handled using subgroup analysis, meta-regression, and sensitivity analysis. Results: Out of 2,100 records, 18 articles were included, with 26,291 total patients. The pooled incidence rate of mortality among TB/HIV coinfected patients was 12.49 (95% CI: 9.24–15.74) per 100 person-years observation (PYO); I2 = 96.9%. The mortality rate among children and adults was 5.10 per 100 PYO (95% CI: 2.15–8.01; I² = 84.6%) and 15.78 per 100 PYO (95% CI: 10.84–20.73; I² = 97.7%), respectively. Age ≥ 45 (PHR 2.58, 95% CI: 2.00– 3.31), unemployed (PHR 2.17, 95% CI: 1.37–3.46), not HIV-disclosed (PHR = 2.79, 95% CI: 1.65–4.70), bedridden (PHR 5.89, 95% CI: 3.43–10.12), OI (PHR 3.5, 95% CI: 2.16–5.66), WHO stage IV (PHR 3.16, 95% CI: 2.18–4.58), BMI < 18.5 (PHR 4.11, 95% CI: 2.28–7.40), anemia (PHR 4.43, 95% CI: 2.73–7.18), EPTB 5.78, 95% CI: 2.61–12.78 significantly affected the mortality. The effect of TB on mortality was 2 times higher (PHR 1.95, 95% CI: 1.19–3.20; I² = 0) than in TB-free individuals. Conclusions: The incidence rate of mortality among TB/HIV-coinfected patients in Ethiopia was higher compared with many African countries. Many clinical factors were identified as significant risk factors for mortality. Therefore, TB/HIV program managers and clinicians need to design an intervention early.